Antimicrobial effect of intracanal substances - Cláudia de Moura Carreira; Silvana Soléo Ferreira dos Santos; Antônio Olavo Cardoso Jorge; José Luiz Lage-Marques (University of São Paulo, 2007)
In some situations, endodontic infections do not respond to therapeutic protocol. In these cases, it is suggested the administration of an alternative intracanal medication that presents a wide spectrum of action and has an in-depth effect on the root canal system. The purpose of this study was to assess the antimicrobial action of ciprofloxacin, metronidazole and polyethylene glycol and natrosol vehicles with different associations and concentrations. The minimum inhibitory concentration (MIC) was determined by using the agar dilution method. The culture media (Müller-Hinton agar) were prepared containing antimicrobial agents at multiple two-fold dilutions of 0.25 to 16 µg/mL, and with the vehicles at the concentrations of 50, 45, 40, 35, 30 and 25%. Twenty-three microbial strains were selected for the study. Metronidazole was not capable of eliminating any of the tested microorganisms. The association of ciprofloxacin with metronidazole resulted in a reduction of the MIC. The vehicle polyethylene glycol inhibited the growth of 100% of the tested strains, while natrosol inhibited 18% of the strains. Ciprofloxacin formulations with polyethylene glycol presented better effects than those of formulations to which metronidazole was added. It was possible to conclude that ciprofloxacin presented antimicrobial action against all tested bacterial strains, and its association with metronidazole was synergic. The vehicle polyethylene glycol showed antimicrobial effect and the ciprofloxacin/polyethylene glycol association was the most effective combination for reducing the tested bacteria and yeasts.